Consumer Buying Interest In Terms Of Advertising On Social Media, Product Uniqueness, And Location (A Comparative Study Of Consumers Of Sosmed Cafe And Tree House Cafe Medan) - Muhammad Valery Maulidzar Siregar; Yossie Rosanty; Elfitra Desy Surya (Penerbit Jurnal Indonesia, 2025)
The cafe business is currently growing rapidly in society, where cafes have now transformed into a part of the habits or lifestyle of groups of individuals. In the business community, for example, cafes have become business meeting locations, where they utilize cafes as places to discuss various aspects of their business in a setting that is not too formal. The visitors come from diverse backgrounds, including entrepreneurs, government and private employees, students, and even certain communities. This study aims to analyze the influence of social media advertising, product uniqueness, and location on consumer purchase interest at Sosmed Cafe and Cafe Rumah Pohon in Medan. Data was collected through surveys using questionnaires distributed to consumers of both cafes. Data analysis was conducted using multiple linear regression. The results of the study indicate that social media advertising, product uniqueness, and location have a significant influence on consumer purchase interest. These findings provide insights for cafe owners in designing effective marketing strategies.